2019
DOI: 10.3390/toxics7020030
|View full text |Cite
|
Sign up to set email alerts
|

Quality Indicators and Possible Ecological Risks of Heavy Metals in the Sediments of three Semi-closed East Mediterranean Gulfs

Abstract: Pollution with copper (Cu), lead (Pb), zinc (Zn), chromium (Cr), and nickel (Ni) heavy metals of the surface sediments collected from three semi-closed East Mediterranean Gulfs, namely Kavala, Strymonikos, and Ierissos Gulfs, North Aegean Sea, Greece, was investigated to evaluate potential benthic ecological risks. The mean concentrations of the studied metals decrease according to the order: Zn > Pb > Cr > Ni > Cu (176.50, 166.23, 127.41, 43.12, and 33.64 mg kg−1 dry weight). Quality indicators an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 45 publications
(68 reference statements)
0
19
0
11
Order By: Relevance
“…According to MPI analysis, in 2017 (MPI > 15) the highest contamination was noted at stations 1, 4, 18, 19, and 20. In 2016, the MPI values were higher than 15 at 11 of the 24 stations: 1, 4, 10,12,14,15,17,19,20,21,22, and 23 (Figure 8).…”
Section: Assessment Of the Contamination Of The Warta River Bottom Sedimentmentioning
confidence: 94%
See 1 more Smart Citation
“…According to MPI analysis, in 2017 (MPI > 15) the highest contamination was noted at stations 1, 4, 18, 19, and 20. In 2016, the MPI values were higher than 15 at 11 of the 24 stations: 1, 4, 10,12,14,15,17,19,20,21,22, and 23 (Figure 8).…”
Section: Assessment Of the Contamination Of The Warta River Bottom Sedimentmentioning
confidence: 94%
“…Water pollution with heavy metals is a common problem, so their concentrations, distribution and sources have been of global interest [15][16][17][18]. The presence of heavy metal pollutants in the water environment has been of great concern because of their established negative effect on the health of humans and state of ecosystems [19][20][21]. Moreover, Wu et al [22] have suggested that future climate changes will increase the harmful effect of heavy metals in water environment because of their release from bottom sediments to water.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, high concentrations of As, Zn, and Mn (320-4100 μgg -1 , 940-4100 μgg -1 , and 3840-26,000 μgg -1 , respectively) have been measured in sediment samples collected close to the coastal mining facilities (Ierissos Gulf) [70]. Furthermore, high concentrations of Cr and Ni have been also measured in surface sediment samples in the area near the load-out facility of the mining operations in Stratoni Bay, and they were considered as the result of the weathering action of the rivers that flow into the Gulf [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, high concentrations of As, Zn, and Mn (320-4100 µgg −1 , 940-4100 µgg −1 , and 3840-26,000 µgg −1 , respectively) have been measured in sediment samples collected close to the coastal mining facilities (Ierissos Gulf) [70]. Furthermore, high concentrations of Cr and Ni have been also measured in surface sediment samples in the area near the load-out facility of the mining operations in Stratoni Bay, and they were considered as the result of the weathering action of the rivers that flow into the Gulf [71,72]. Additional studies that have included water samples from Ierissos Gulf and soil samples from the Stratoni area have shown exceedances of the World Health Organization (WHO) limit values and of the global soil mean values, respectively, mainly for the elements As, Sb, Cr, Ni, Cd, Pb, Mn, and Fe [43,45,[73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…Solubilization, speciation, precipitation, as well as diffusion and advection, are also critical processes that determine the spatial distribution of PTE in water bodies [1]. For these reasons, sediments have been widely used as indicators of the environmental quality of aquatic ecosystems [4][5][6][7][8][9]. They provide essential information about the historical record and functionality of these environments.…”
Section: Introductionmentioning
confidence: 99%